A dual mesh finite domain method for steady-state convection–diffusion problems. (15th January 2021) - Reddy, J.N.; Martinez, Matthew
Abstract: The dual-mesh finite domain method (DMFDM) proposed by Reddy (2019)[1] is used to study the steady-state convection–diffusion problems in 1D and 2D. In the DMFDM, one mesh of finite elements for the approximation of the domain and primary variables and another mesh of control domains, which also covers the whole domain, to satisfy the governing differential equations are used. The approach is distinguished from both the finite element method and the finite volume method, although the method shares the desirable features of both methods. Numerical examples are presented to illustrate the methodology and accuracy compared to the finite element and finite volume solutions.